BPR Syari'ah di Mata Masyarakat: Studi Kasus pada BPRS al-Mabrur Ponorogo - Khusniati Rofiah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2007)
This study aims to analyze public perceptions of the existence and role of Islamic Rural Banks (BPR Syariah, BPRS) in the Islamic financial system, with a case study of BPRS al-Mabrur Ponorogo. This study highlights the factors that influence public trust, the level of service utilization, and the challenges faced by BPRS in increasing sharia financial inclusion. The research method used is a descriptive-qualitative approach with data collection techniques through interviews, observations, and document studies. The results showed that the community has a positive view of the sharia principles applied by BPRS, but there are still limitations in financial literacy and service accessibility. The main factors that encourage community participation are transparency, product halalness, and ease of access to financing. This study recommends improving sharia financial education and optimizing marketing strategies so that BPRSs are more competitive and inclusive in serving the community.